On the Blast Mitigation Ability of Multiple V-Shape Deflectors - Sebastian Stanisławek; Andrzej Morka (Shock and Vibration)
This paper presents a 2D numerical study of v-shape deflectors subjected to high explosive charge detonation. The literature provides many papers concerning the appropriate geometry of blast protection deflectors. Such structures require a relatively high distance between the ground and the vehicle chassis. In most cases, the placement of a deflector is not possible or it cannot cover the whole area under a chassis. An interesting question that arises is to what extent a set of small deflectors would be able to mitigate blast effects. The content of this paper constitutes an answer to this question. Three analyses were conducted: (1) multiplication of triangle components, (2) effect of deflector size, and (3) geometry-induced shock dynamics. The problem was solved with the use of modelling and simulation methods, in particular, CFD-FEM implemented in the LS-DYNA code. It was considered a plain issue in computational fluid dynamics, where space discretization for each option was built with two-dimensional elements to ensure efficient calculations. Deflectors were described using a rigid wall boundary condition, and an adequate simplified detonation model was assumed. The primary measure of the results was reaction force history, with momentum transfer and pressure distribution maps considered supplementary. The studies performed showed that both minimizing the v-shape deflector size and surrounding it with adjacent structures had a negative impact on its blast mitigation effectiveness. However, for each multi-v-shape deflector, some improvement was present, and, therefore, in situations where the installation of a typical protector is not possible due to dimensional requirements, it may offer a compromise solution.